Use of sedating medications around nursing home admission in Denmark. Issue 11 (22nd August 2021) - Pottegård, Anton; Lundby, Carina; Jarbøl, Dorte Ejg; Larsen, Søren Post; Hoppe, Bettina Clauber; Hoffmann, Helene; Thompson, Wade
Abstract: Purpose: To examine use of sedating medications around the time of nursing home admission in Denmark. Methods: We conducted a register‐based drug utilization study, describing patterns of commonly used medications with sedative effects leading up to and after nursing home admission using data from 94 Danish nursing homes between 2015 and 2017. Results: We identified 5179 residents (median age 84 years, 63% female) and described monthly incidence and total use of benzodiazepines (BZDs), Z drugs, mirtazapine/mianserin, quetiapine, promethazine, and melatonin. The proportion of unique users of sedating medications was similar before and after admission (42% before vs. 40% after) despite an increase in total use after admission. The overall incidence of sedating medications peaked in the 6 months before and 6 months after admission (peaking at 4.6 per 100 person‐months 1 month after admission). The most commonly initiated medications were mirtazapine/mianserin, followed by BZDs and Z drugs. Total use of sedating medications increased leading up to admission (peaking at 1001 defined daily doses per 100 residents per month 1 month after admission) and decreased gradually after admission. Conclusions: Sedative medication initiation increases sharply leading up to admission in Danish nursing homes. Mirtazapine/mianserin is a commonly used agent in nursing homes, despite limited evidence on benefits and harms. Efforts to promote rational use of these medications in nursing homes remain warranted.